From cell to heart: the impact of the cell organelles dysfunction on heart disease. Issue 4 (April 2018) - Tsipis, Angelos; Athanassiadou, Anna M.; Petrou, Emmanouil; Miliopoulos, Dimitris; Athanassiadou, Pauline; Kavantzas, Nikolaos; Athanassopoulos, George
Abstract : N/A: Cellular morphology reflects biologic behavior and activity of the tissue and of the organ also reflects the genetic and molecular biology of the cells themselves. This intermediary position places examination of the cell in a key role to our understanding of the innumerable processes that affect this closely knit chain, from molecules to host. A large volume of the cell is occupied by organelles that come in a variety of shapes and sizes. Organelles are dynamic to maintain homeostasis and adjust to the various functions of the cell. The cardiovascular system is metabolically very active and is therefore particularly vulnerable to defects of the cellular substructures, such as the mitochondrial respiratory chain. Given the functional complexity of the cardiovascular system, it is not surprising that defects in cell organelles produce diverse clinical manifestations. Organelle dysfunction is being recognized as the basis of a wide variety of heart diseases. In this review, the authors discuss the relationship between organelle structure and function in myocardial cells and how these organelles have been linked to the cardiovascular diseases.